IMPACT OF CSR IN INDIAN SOCIETY - Shaikh, Mohammed Sameer (ShodhKosh: Journal of Visual and Performing Arts, 2022)
In today’s era, there is significance to CSR, provided in the society and there are some firm boundaries that have been extended. Corporate Social Responsibility is not a trend, whereas it is considered as a commerce imperative which some Indian companies are starting to consider and engaging with it in some way. The study has focused on the impact of CSR on healthcare in Indian society. The study has highlighted the top healthcare projects in India by CSR. The research study also has focused on the impact of CSR on education in Indian society. The study has also highlighted the top education projects funded in India by CSR. Study has highlighted the benefits and drawbacks of CSR (Corporate Social Responsibilities). For the study qualitative and quantitative data was used and data has been collected by questionnaire method and this research study has collected sample of 100 respondents, 100 respondents from Mumbai region only. It was observed that CSR has impacted Indian Society.